2015
DOI: 10.4209/aaqr.2013.09.0297
|View full text |Cite
|
Sign up to set email alerts
|

Water Soluble Ionic Components in Particulate Matter (PM10) during High Pollution Episode Days at Mohal and Kothi in the North-Western Himalaya, India

Abstract: Particulate pollutants and their water soluble ionic components were collected and analyzed on the occasion of high pollution episode days in the period 2009 to 2011. Among the water soluble ionic constituents at Mohal (valley base), SO 4 2-(34%) was the largest contributor; followed by Cl -(20%), NO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Moreover, this ratio indicates the influence of sulfuric acid, reflecting the contribution of acidity in the atmosphere. Furthermore, a recent study from north-western Himalaya, India [43] suggested that the ratio of such acids >1 means free acidity due to nitric and hydrochloric acid. Meanwhile, seasonally the ratios were found in the order of monsoon (1.01) > winter (0.50) > pre-monsoon (0.43) > post-monsoon (0.31).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Moreover, this ratio indicates the influence of sulfuric acid, reflecting the contribution of acidity in the atmosphere. Furthermore, a recent study from north-western Himalaya, India [43] suggested that the ratio of such acids >1 means free acidity due to nitric and hydrochloric acid. Meanwhile, seasonally the ratios were found in the order of monsoon (1.01) > winter (0.50) > pre-monsoon (0.43) > post-monsoon (0.31).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Similar height has been applied by Kuniyal et al (2013) to study the composition and transport of aerosols in north western Himalayan region of India. Total six clusters were identified viz.…”
Section: Clusterwise Chemical Composition Of Snowmeltmentioning
confidence: 99%
“…In spite of its sensitivity, annual and seasonal depositions of various chemical species are poorly understood. There are some, by far very few, papers on the aerosols, rain water and snow geochemistry in the Himalayas (Gajananda et al, 2005;Tiwari et al, 2012;Kuniyal et al, 2013). Also, the comprehensive studies on fresh snowfall chemistry are limited in western Himalayan region of India (Naik et al, 1995;Kulshrestha and Kumar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SO 2 and NO x owing to its gas to particle conversion under optimum conditions have been studied widely for different categories of biomass (Reddy and Venkataraman, 2002;Gadi et al, 2003;Saud et al, 2011). Kuniyal et al (2015) studied the particulate concentration in the Kullu valley (Himalayan region) and reported that coal, wood and straw burning could be the reason for the particulate concentration over the region. The major source of fluoride and potassium in the Himalayan region is possibly due to burning of wood and straw.…”
Section: Introductionmentioning
confidence: 99%